1989
DOI: 10.1227/00006123-198908000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Meningiomas: Review of 174 Operated Cases

Abstract: The long-term results obtained in a series of 174 patients operated on for spinal meningiomas are critically analyzed. This series was similar to those of other authors with regard to age, sex, location of the tumors, and clinical presentation. Before surgery, about 70% of the patients were included in Groups I and II (mild neurological impairment), and about 30% of the patients were classified in Groups III and IV (significant to severe neurological impairment, up to paraplegia). Complete tumor removal was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
328
3
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 358 publications
(366 citation statements)
references
References 0 publications
23
328
3
6
Order By: Relevance
“…Twenty-eight of thirty meningiomas were in the thoracic region, and the remaining two were in the cervical region. Solero et al [13] published a report of four meningiomas of the lumbar region, and found the frequency in men and women was equal.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Twenty-eight of thirty meningiomas were in the thoracic region, and the remaining two were in the cervical region. Solero et al [13] published a report of four meningiomas of the lumbar region, and found the frequency in men and women was equal.…”
Section: Discussionmentioning
confidence: 97%
“…In one series, lumbosacral meningiomas represented only 2.3% of cases among 705 spinal meningiomas [4]. In two other series meningiomas in patients 70 years or older represented a maximum of 10% of all spinal meningiomas [10,13]. Morandi et al [8] has published the only clinical series of elderly patients with meningioma.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations